Midterm treatment results of medial epicondyle fractures of the humerus in children - Belhan, Oktay; Karakurt, Lokman; Yilmaz, Erhan; Serin, Erhan; Incesu, Mustafa; Bulut, Mehmet (Turkish Joint Diseases Foundation, 2007)
Objectives: We evaluated the results of conservative treatment and surgical treatment performed in appropriate indications in children with medial epicondyle fractures of the humerus. Patients and methods: The study included 24 patients (18 males, 6 females; mean age 11.6 years; range 9 to 14 years) who had medial epicondyle fractures of the humerus due to elbow injuries. The fractures were on the right side in nine patients, and on the left in 15 patients. Patients with fracture displacement of <5 mm and >= 5 mm were treated conservatively (n=8) and with open reduction-internal fixation (n=10), respectively, while six patients with old or comminuted fractures were treated with epicondylar excision. The results were assessed as good, fair, or poor according to clinical and radiographic findings. The mean follow-up was 30.2 months (range 13 to 42 months). Results: The results were good in six patients, fair in two patients in the conservative treatment group; good in eight patients, fair in two patients in the open reduction-internal fixation group; and fair in three patients, poor in three patients in the excision group. Fibrous nonunion was observed in two patients treated conservatively, and in one patient treated with internal fixation, but none resulted in functional loss. The results of epicondylar excision were significantly worse compared to conservative treatment (p=0.01) and open reduction-internal fixation (p=0.004), but the results of the latter two were similar (p>0.05). Conclusion: Successful results can be obtained with conservative methods and open reduction with internal fixation in the treatment of medial epicondyle fractures of the humerus. Epicondylar excision should be avoided because of high complication rate and poor results.
Keywords: children; elbow/injuries; elbow joint/surgery/radiography; fracture fixation; internal; humeral fractures